Two Novel Freeze-Dried pH-Sensitive Cyclosporine A Nanoparticles: Preparation, in vitro Drug Release, and in vivo Absorption Enhancement Effects - Zhi-gang, Fang; Ping, Pan; Zhi-qiang, Yang; Ya-gen, Chen; Jian-kang, Zhang; Miao, Wei; Xue-nong, Zhang; Qiang, Zhang (Current Nanoscience, 2009)
The present study was aimed at preparation and performance evaluation of pH-sensitive cyclosporine A (CyA) nanoparticles (CyA-NPs) to improve the poor bioavailability of lipophilic CyA. CyA-NPs were prepared with two types of Eudragit® copolymers (Eudragit ® S100 and Eudragit® L100) by a quasi-emulsion solvent diffusion technique. Freeze-dried formulations (Lac-CyA-S100-NP and Lac-CyA-L100-NP) were also prepared. The physical properties, particle size, encapsulation efficiency, and in vitro drug release characteristics were studied. The in vivo bioavailability of CyA-NP and Lac-CyA-S100-NP was investigated in rats at a dose of 15 mg/kg and compared with that of the commercial formulation, Sandimmune Neoral®. The mean particle size of the CyA-NPs was less than 50 nm, and the encapsulation efficiency was over 99%. Characteristics of the freeze-dried nanoparticles were found to remain relatively stable when lactose was used as a cryoprotectant. In vitro release studies revealed that the CyA-NPs exhibited significant pH-sensitivity. The relative bioavailabilities of CyA-L100-NP, CyA-S100-NP, and Lac-CyA-S100-NP were 117.3%, 162.1%, and 130.1%, respectively, when compared with that of Neoral®. Therefore, CyA-NPs were considered to be promising oral delivery systems for enhancement of the absorption of the poorly soluble drug, CyA. Freeze-dried nanoparticles could be developed into a novel and effective CyA formulations.
Keywords: pharmacokinetics